INVISIBLE WALLS: UNCOVERING HEALTHCARE ACCESS BARRIERS FOR PERSONS WITH DISABILITIES IN BAHAWALNAGAR (Contemporary Journal of Social Science Review, 2025)
The aim of this study is to identify the key factors that create barriers in accessing healthcare services for persons with disabilities in District Bahawalnagar. A qualitative research approach was employed, in which data were collected from key stakeholders—including doctors, paramedical staff, and individuals with disabilities—through structured interviews and focus group discussions. Thematic analysis of the responses led to the identification of twelve core themes representing the major challenges faced by disabled individuals in availing healthcare services. These include economic constraints, physical mobility limitations, infrastructural barriers, discriminatory practices, and communication gaps, among others. The findings highlight critical systemic and social shortcomings that need to be addressed to ensure inclusive and equitable healthcare access. Based on the study’s outcomes, it is recommended that the Health Department formulate disability-inclusive policies and design service delivery operations specifically tailored to meet the unique needs of persons with disabilities in the district.